Longitudinal Intergenerational Birth Cohort Designs: A Systematic Review of Australian and New Zealand Studies. - Michelle L Townsend; Angelique Riepsamen; Christos Georgiou; Victoria M Flood; Peter Caputi; Ian M Wright; Warren S Davis; Alison Jones; Theresa A Larkin; Moira J Williamson; Brin F S Grenyer (PLoS ONE)
Background The longitudinal birth cohort design has yielded a substantial contribution to knowledge of child health and development. The last full review in New Zealand and Australia in 2004 identified 13 studies. Since then, birth cohort designs continue to be an important tool in understanding how intrauterine, infant and childhood development affect long-term health and well-being. This updated review in a defined geographical area was conducted to better understand the factors associated with successful quality and productivity, and greater scientific and policy contribution and scope. Methods We adopted the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach, searching PubMed, Scopus, Cinahl, Medline, Science Direct and ProQuest between 1963 and 2013. Experts were consulted regarding further studies. Five inclusion criteria were used: (1) have longitudinally tracked a birth cohort, (2) have collected data on the child and at least one parent or caregiver (3) be based in Australia or New Zealand, (4) be empirical in design, and (5) have been published in English. Results 10665 records were initially retrieved from which 23 birth cohort studies met the selection criteria. Together these studies recruited 91,196 participants, with 38,600 mothers, 14,206 fathers and 38,390 live births. Seventeen studies were located in Australia and six in New Zealand. Research questions initially focused on the perinatal period, but as studies matured, longer-term effects and outcomes were examined. Conclusions This review demonstrates the significant yield from this effort both in terms of scientific discovery and social policy impact. Further opportunities have been recognised with cross-study collaboration and pooling of data between established and newer studies and international studies to investigate global health determinants.